Analisis Risiko Harga pada Usahatani Tomat di Nagari Alahan Panjang Kabupaten Solok - Rihadatul Aisy; Nofialdi; Afrianingsih Putri (JOSETA Journal of Socio-economics on Tropical Agriculture, 2025)
Tomatoes are valuable horticultural commodities with numerous benefits, but are highly vulnerable to price instability. This study analyzes price risk and management strategies in tomato farming in Nagari Alahan Panjang, Solok Regency. The research aims to identify sources of price risk, measure its level, and formulate effective management strategies. The ARCH/GARCH model is applied to forecast tomato price volatility, while variance, standard deviation, and the coefficient of variation determine the magnitude of risk. Results show that significant price drops and fluctuations occurred in April, September, and October 2022, with a coefficient of variation of 0.53, indicating a high level of price risk. Farmers in Alahan Panjang adopt two main strategies to manage this risk: preventive and mitigation. Preventive measures include better crop maintenance and intercropping, while mitigation efforts involve continuous harvesting, post-harvest processing, crop rotation, and delaying harvests to minimize losses caused by market fluctuations.